THE EFFECTIVENESS OF MULTICULTURAL BASED INDONESIAN TEACHING MATERIALS TO IMPROVE CRITICAL THINKING SKILLS - Sony Ari Wibowo; Murtono; Sri Utaminingsih (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to describe the effectiveness of multicultural-based Indonesian teaching materials to improve students’ critical thinking skills at grade IV elementary schools in Kabupaten Jepara. The type of this study was Research and Development (R & D). The teaching materials weretested at grade 1 SD Tritis and SD 1 Karangnongko as the experiment groups and SD 1 Daren and SD 3 Nalumsari as the control groups. Datacollection was conducted through observation, interviews, and documentation. Indonesian teaching materials were developed based on themulticultural based Indonesian teaching materials on the theme 4 “various jobs”at grade IV elementary school. Results showed that multiculturalbased Indonesian teaching materials was effective to enhance the students’ critical thinking skills at grade IV elementary schools in KabupatenJepara. The results of t-test on the experimental and control groups was 8.994, which indicated that tcount >ttable (8.994 > 1.699). Hence, Ho wasrejected and Ha was accepted. Based on this result, it could be concluded that utilizing multicultural based Indonesian teaching materialswas effective and fit to improve the students’ critical thinking skills at grade IV elementary schools in Kabupaten Jepara.